Bike share. - Fishman, Elliot (Routledge, 2020)
There are now over 2,000 cities with a bike share program. Bike Share examines all the major developments in the 50-year history of bike share. The book provides a detailed focus on contemporary bike share programs, including many of the most prominent systems, such as those in Paris, London, and New York, as well as the rapidly emerging dockless bike share sector. This book also addresses how rapid technological innovation, particularly in terms of mobile internet devices and electric assist bicycles may change the face of not just cycling, but urban mobility more generally. By the end of 2018 it was estimated that there are more than 20 million bicycles in the global bike share fleet, with most of these dockless, coming online only in the last three years. Consequently, research examining bike share has not kept pace with the rapid deployment of this new form of urban mobility.
Keywords: Stadtverkehr; Fahrradverkehr; Fahrradverleih; Technische Infrastruktur; Verkehrsinfrastruktur; Städtevergleich; Bike sharing